Prospects of exercising teacher agency in facing students’ learning difficulties - Yuni Budi Lestari; Kamaludin Yusra; Nurachman Hanafi; Nawawi Nawawi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Teacher agency is generally accepted as a strategy that teachers employ to face educational challenges. This article presents the result of a qualitative case study that examined learning difficulties that university students face during their study and prospects of exercising agency in facing the students’ learning difficulties. The current study was conducted at a postgraduate English department in a government University in West Nusa Tenggara. The participants of this study include three students in their third semester in the academic year 2020/2021 and three university English teachers who were purposively selected. Being qualitative in nature, this study used in-depth interviews with the students to obtain data on their learning difficulties. In-depth interviews were also conducted to the university English teachers to collect data on prospects of exercising their agency in dealing with learning difficulties facing the students. The collected data were then analyzed using the following steps: identifying, classifying, describing, and explaining. Data analysis indicated that the students experienced difficulties in reading and writing. The results of the study also revealed prospects of teacher agency exercise in helping students cope with their learning difficulties as enabled by specific conditions related to teachers’ pedagogical knowledge and teachers’ collaborative cultures.